Low-energy Selective Laser Trabeculoplasty Repeated Annually: Rationale for the COAST Trial. Issue 7 (7th July 2021) - Realini, Tony; Gazzard, Gus; Latina, Mark; Kass, Michael
Abstract : The recent Laser in Glaucoma and Ocular Hypertension Trial provided the evidentiary basis for a paradigm shift away from the historical medication-first approach to glaucoma–which has numerous limitations, the most important of which is poor adherence to therapy –and toward a laser-first approach. Now 20 years after its commercialization, selective laser trabeculoplasty (SLT) is routinely performed consistently with its initial description, with energy titrated to the appearance of fine, champagne-like cavitation bubbles. A recent data set suggested that lower energy SLT, applied as primary therapy and repeated annually irrespective of intraocular pressure–rather than pro re nata when its effect wanes and irrespective of intraocular pressure rises –yields longer medication-free survival than standard energy SLT repeated pro re nata. A new study–Clarifying the Optimal Application of SLT Therapy –has been initiated to explore this preliminary finding in a pair of consecutive randomized trials. Herein, we provide an evidence-based rationale for the use of low-energy SLT repeated annually as primary therapy for mild to moderate primary open-angle glaucoma or high-risk ocular hypertension.